"It's a radical decision not to use words": Partnering with wordless picture books to enhance reading and writing. Issue 4 (8th August 2022) - Giorgis, Cyndi; Johnson, Nancy J.
Abstract: In using wordless picture books, teachers enhance the reading experience while fostering, nurturing, and broadening students' reading and writing skills. Wordless picture books are accessible to all students. They encourage and require readers to slow down as they inhabit and comprehend the story told through art, symbolism, and images. Picture books often carry a stigma that they are for students in elementary grades and certainly not for young adolescents. However, many recent wordless picture books are multifaceted, thought-provoking, and galvanizing, making them perfect for an older audience. How can middle school educators bring these books into their classrooms in positive, meaningful, and inspiring ways? This article offers the rationale for partnering with wordless picture books to prompt creative writing, enhance vocabulary, increase background knowledge, foster comprehension, and elevate visual literacy. Coupled with recommended titles of wordless picture books for adolescents, an instructional strategy will demonstrate to students how to slow down, savor, and interpret both art and narrative storytelling.